2016
DOI: 10.1186/s12890-016-0189-1
|View full text |Cite
|
Sign up to set email alerts
|

Impaired nuclear factor erythroid 2-related factor 2 expression increases apoptosis of airway epithelial cells in patients with chronic obstructive pulmonary disease due to cigarette smoking

Abstract: BackgroundCigarette smoking-induced oxidative stress is known to be a key mechanism in COPD pathogenesis. Nuclear factor erythroid 2-related factor 2 (Nrf2) is a central transcription factor that regulates the antioxidant defense system. The aim of this study was to compare Nrf2 expression in COPD subjects and control subjects, and to determine the role of Nrf2 in protecting against oxidative stress-induced apoptosis.MethodsWe enrolled 8 COPD subjects and 7 control subjects in this study. We performed bronchia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 41 publications
5
47
0
Order By: Relevance
“…CSE-induced apoptosis was significantly higher in the 15% CSE group than the control group at 12 hours, as observed in our previous study 14. In contrast, apoptosis was significantly lower in the groups pretreated with 30 or 60 ng/mL irisin than in the 15% CSE-only group (Figure 4B; P <0.05 and P <0.01, respectively).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…CSE-induced apoptosis was significantly higher in the 15% CSE group than the control group at 12 hours, as observed in our previous study 14. In contrast, apoptosis was significantly lower in the groups pretreated with 30 or 60 ng/mL irisin than in the 15% CSE-only group (Figure 4B; P <0.05 and P <0.01, respectively).…”
Section: Resultssupporting
confidence: 86%
“…Cells were then subjected to CSE-induced apoptosis analyses via a time-lapse cell-imaging assay using the IncuCyte Zoom system with CellPlayer 96-well kinetic caspase 3/7 reagent (Essen BioScience, Ann Arbor, MI, USA), as previously described 14. The apoptotic index was calculated according to the equation: Apoptotic index=Apoptotic cell numberTotal cell numberCSE was prepared as previously described 14. Cells were stimulated with 10% or 15% CSE diluted with cell-culture medium and pretreated with 15, 30, or 60 ng/mL irisin (ADI-908-307; Enzo Life Sciences, Farmingdale, NY, USA), referring to the irisin levels of controls and subjects with COPD in our previous study 7…”
Section: Methodsmentioning
confidence: 99%
“…Under physiological conditions, Nrf2 is bound to its natural inhibitor Kelch-like-ECH-associated protein 1 (Keap1) in the cytoplasm [25]. In the presence of oxidative or xenobiotic stimuli, Nrf2 dissociates from Keap1 and translocates into the nucleus, where it binds to the antioxidant response element, and initiates the transcription of anti-oxidative genes encoding the respective proteins such as SOD, CAT, GPx and heme oxygenase-1 [26]. Deficiency of Nrf2 was shown to exacerbate cerebral infarction and neurologic deficits in animal models [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…() found that CSE interfered with the normal functions of mitochondria in A549 cells by inhibition of complex I and II activities in the electron transport chain and impairment of mitochondrial membrane potential, reducing the ability of mitochondria to synthesize ATP, which prevented apoptosis and caused necrosis. Contrary to these results, some other studies (Jiao, Ao, & Xiong, ; Ramage, Jones, & Whelan, ; Yamada et al., ) showed that CS provoked apoptotic cell death in A549 cells. An increase in CS‐induced apoptosis was related to the impairment of nuclear factor erythroid 2‐related factor (Nrf2), suggesting that an inappropriate antioxidant response and excessive apoptosis could result in lung tissue destruction and emphysema (Yamada et al., ).…”
Section: Discussionmentioning
confidence: 56%